ENGINEERING MANAGER'S HANDBOOK an insider's guide to managing software development and engineering teams - Evans, Morgan (Packt Publishing Ltd., 2023)
A comprehensive guide to engineering management packed with tips, tricks, and techniques to drive results Key Features Acquire the necessary skills to manage engineers across various settings Gain valuable insights into engineering leadership, people management, and driving organizational change Discover pitfalls to avoid as a new engineering manager and understand their causation Purchase of the print or Kindle book includes a free PDF eBook Book Description Producing delightful and customer-centric digital products has become a standard expectation across businesses. Engineering managers are uniquely positioned to make a huge impact on the success of products and the software systems that power them. With the help of this guide, teams and companies can develop meaningful and maintainable systems. This book facilitates you to find your footing as an engineering manager, develop a leadership style, balance time between engineering and managing, build successful and sustainable engineering teams in different settings, and work within constraints without sacrificing technical standards or team empathy. You'll learn practical techniques for establishing trust and authority, allowing you to create a cohesive and high-performing engineering team. You'll discover effective strategies to strike the right balance between contributing to technical work and collaborating with your team, ensuring optimal productivity and collaboration. By the end of this book, you'll have the tools and knowledge necessary to thrive as an engineering manager. Whether you're just starting out in your role or seeking to enhance your leadership capabilities, this handbook empowers you to make a lasting impact and drive success in your organization. What you will learn Avoid pitfalls that are common to new managers Understand how to establish trust and authority Explore methods and tools for building world-class engineering teams Discover how to build a great reputation as a leader Avoid costly missteps that end up requiring re-work Increase employee retention on your team Facilitate better product outcomes Gain insights from key studies and reference material Who this book is for This book is a valuable resource for software engineers and developers transitioning into engineering management roles, equipping you with best practices and insights to navigate the new responsibilities effectively. Whether you're a newly promoted engineering manager or an experienced one seeking immediate answers to challenges, this comprehensive and up-to-date guide provides the support you need. Familiarity with the software development lifecycle, including concepts like version control, code review, and deployment, is required.